DIGITAL FORENSICS IN JOURNALISTIC INVESTIGATIONS AS A TOOL FOR TRACKING HIDDEN PROCESSES - Степовий, Олег (SWorldJournal, 2026)
The article is devoted to the hidden aspects of the functioning of digital processes, which become the object of analysis within the framework of journalistic investigations. The purpose of the article is to analyze the role of digital forensics in journa